From block to shred: Understanding the factors influencing shreddability of mozzarella cheese - Gunvantsinh Rathod; Suresh Sutariya; Ram Kumar; Praveen Upreti; Prafulla Salunke; J.K. Amamcharla (Journal of Dairy Science)
ABSTRACT: Mozzarella cheese is widely used for pizza applications, and it is generally shredded either in conversion plants or in pizzerias. The shreddability of mozzarella cheese is influenced by a variety of factors, and it is critical to understand how different mozzarella cheese types and storage conditions (temperature and age) affect this property. Three batches each of 3 types of mozzarella cheese (low-moisture mozzarella [LMM], low-moisture part-skim mozzarella [LMPS], and reduced-fat mozzarella [RFM]) representing 3 different fat levels were procured directly from a commercial manufacturer and stored at 2 different temperatures (1.67 and 4.44°C) and evaluated for shreddability at 2- and 3-wk storage. Shreddability parameters such as stiction (peak force) and work of grating were significantly affected by fat content and storage time, whereas the weight of the shred obtained after each cycle was significantly affected by fat content and storage temperature. Along with shreddability, other tests, such as texture profile analysis (TPA), wire cutting, stretchability, and dynamic shear rheology (DSR) were performed to understand their relationship with shreddability. Textural parameters were significantly affected by fat content and storage time, whereas wire cutting parameters were significantly affected by fat content, storage time, and temperature. Stretchability and dynamic shear rheology parameters were significantly affected by fat content followed by storage time and temperature. Further shreddability parameters, such as stiction and work of shear had a positive significant correlation, whereas the weight of shreds had a negative significant correlation with unmelt (TPA) and melt parameters (stretchability and DSR). Overall, fat content had the greatest effect on shreddability followed by storage time and temperature. Considering the high correlation of shreddability with other textural parameters, textural parameters can be used to predict shreddability of mozzarella cheese.